The Joy of JavaScript - Atencio, Luis (Manning Publications, 2021)
The Joy of JavaScript introduces techniques that turn JavaScript programmers into JavaScript pros. You'll work with cutting edge APIs, language features, and coding styles to tackle tricky problems in an elegant manner. Along the way, you'll practice good object design, drive business logic with functional thinking, and untangle complex data flows.